Customer Satisfaction Analysis and Assesment of Occupational Health & Safety and Environment in Building Construction Project - Silvana; Hasibuan, Bernard; Sugiarto (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
Ensuring safe working environment, reducing accident risks and safeguarding the workers and communities’ health are critical in construction projects. Customer satisfaction of Occupational Health, Safety and Environment is essential to project success since satisfied consumers are more likely to trust and loyal to contractor. WEGE has experienced client satisfaction issues over the last two years, including subpar job quality and project delays. Occupational Health & Safety and Environment performance data demonstrate the existence of workplace accidents, which must be addressed to improve customer satisfaction and ensure business operations sustainability. Direct survey approach was employed in this study to collect samples from current populations. The population comprises 169 people who are clients of the building construction project, both internally and externally. Utilizing proportionate stratified random sampling with a sample size of 119 respondents, the sampling methodology applies the Slovin formula. Using the Customer Satisfaction Index (CSI) approach, the findings indicated that 79.17% of the total satisfaction was rated satisfactory. The Occupational Health, Safety and Environment report's orderly administration indicator had the largest gap analysis result (-0,24), while the rubbish and waste management indicator had the lowest gap value (-0,59). It is interpreted that the higher the gap score, the greater the priority for attribute improvement. The spider chart's outcome illustrates that relevance of performance level remains higher than it is currently. Specifically, the "Occupational Health, Safety and Environment report administration order" criterion has the lowest value. Consequently, the order of project report administration prior to the project's commencement is recommended as a means of enhancing customer satisfaction with the Occupational Health, Safety and Environment building construction projects aspect.